Analisis Implementasi Model Pembelajaran Inkuiri Dalam Mengembangkan Keterampilan Proses Sains Pada Pembelajaran IPA di SD Swasta Pelangi Medan - Yoslin Wijaya; Nurhairani; Elvi Mailani; Fahrur Rozi; Laurensia Masri Perangin-angin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This qualitative case study at Pelangi Private Elementary School Medan examines the integration of inquiry learning in science, its impact on students' Science Process Skills (SPS), and its institutional factors. Utilizing interviews, observations, and documentation from the principal, fourth-grade teacher, and students, data were analyzed via the Miles, Huberman, and Saldaña framework. Findings reveal that the structured inquiry stages—from problem presentation to drawing conclusions—significantly enhanced students' SPS, particularly in formulating hypotheses, controlling variables, and conducting experiments. Teacher readiness, adequate facilities, and student enthusiasm acted as key facilitators. Conversely, limited prior knowledge, restricted instructional time, and low learning independence emerged as primary barriers. Ultimately, this study demonstrates that inquiry learning effectively develops students' SPS, provided that continuous teacher scaffolding is maintained.